Trespasse: uma análise crítica no ordenamento jurídico brasileiro - Couto Filho, Fábio Costa (2022)
The present study deals with the contract of alienation of the establishment, the so-called trespass. It describes all the nuances in this kind of adjustment to the Brazilian legal system, that is to say, all the steps necessary for the fulfillment of the objective of this kind of adjustment. In addition to the discussion of the practical aspects laid down in the Brazilian civil legislation, a critical analysis of the legal requirements is also made. Such requirements result, in most cases, in an option in the market for the economic transfer of the establishment via transfer of societal participation in favor of the one who intends to buy the property, without there strictly being, from a legal point of view, any change in the ownership of the set of goods represented by the establishment. In the criticisms, as well as in the descriptions of foreign systems, especially the Italian system, some suggestions, albeit shy ones, appear of new laws. In any case, the main contribution of this work is to revisit the peculiarities of the institute in the current state of Brazilian legal dogma, even as a way of reaffirming the importance of this particular set of goods that is the establishment, a true business tool developed by the businessman